Examining Gender Dimensions of Leadership in International Nonprofits. (2nd January 2021) - Kolpakov, Aleksey; Boyer, Eric
Abstract : Do male and female executives approach leadership in similar ways? What do their approaches reveal about their potentials for addressing contemporary leadership challenges and promoting leadership ascension? While considerable research has been conducted on the ways that gender influences leadership styles, the issue has received limited attention in the nonprofit sector. This research provides a unique perspective on the ways that male and female executives align their leadership approaches with gendered constructs of leadership outlined in the agentic-communal framework. The results indicate that while male and female leaders adhered to many aspects of the gendered domains of the framework, there were some notable exceptions. Female executives were generally more likely to adopt interpersonal approaches to leadership, and while common aspects of executive leadership reflected masculine constructs of leadership traits, male and female executives displayed more variance in their approaches to leadership skills and behaviors.